Morgan le Fay : The Inheritance of the Goddess - Martins, Ana Rita (2017)
“Morgan le Fay: The Inheritance of the Goddess” will analyze Morgan le Fay’s character in Arthurian narrative during the Middle Ages. Starting from a research on the Celts and their culture, this article aims to prove that Morgan le Fay’s origin might be traced back to Celtic goddesses due to the characteristics she shares with the Celtic goddesses The Morrígan and Modron. However, Morgan is only mentioned for the first time, in 1150, in the work Vita Merlini by Geoffrey of Monmouth, where she is named Morgen. Queen of the Otherworldly island Avalon she possesses solely positive traits. Therefore, this study’s goal is also to explain why Morgan le Fay was transformed into one of the greatest villains of Arthurian texts. To reach this goal, some of the main English medieval literary will be analyzed as well as other social and cultural factors.